From Disciplines to Dialogue: Research and Writing as a Dynamic Duo for Interdisciplinary Collaboration - Hendriks, Anne Lou; Hendriks, Alvyn Cesarianto (12th International Scholars Conference 2025, 2026)
Despite being seen as distinct academic disciplines, research and writing work together in interdisciplinary teams. While research is a systematic process of inquiry aimed at finding new knowledge, solving problems, or deepening understanding of a particular topic, and writing is a cognitive and social space where disciplinary perspectives are negotiated and integrated, and little is known about how writing serves as an active, integrative process that shapes and advances interdisciplinary research collaboration beyond its role as a mode of dissemination. This phenomenological study explores the views of four university teachers on their lived experiences of how interdisciplinary collaboration—the integration of theories, methods, and concepts from multiple disciplines—creates new frameworks or solutions in research and writing for a dynamic duo. The themes that emerged from the study included collaborative knowledge-building via writing, bridging disciplinary divides, synergistic collaboration fostering breakthroughs, and shifting viewpoints. These findings indicate that interdisciplinary collaboration fosters mutual learning, innovation, and transformative understanding through co-writing, negotiation of differences, and integration of diverse perspectives.